Current and Evolving Practices in the Quality Control of Cosmetics - Dodou, Kalliopi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cosmetic products undergo nowadays rigorous Quality Control testing to ensure that they are safe and stable and that their claims are substantiated by scientifically robust data. Quality Control tests used in the pharmaceutical industry can be applicable also for cosmetic formulations. However, claim substantiation testing is unique to cosmetic products. To enable time- and cost-effective quality control testing, assessment methodologies constantly keep evolving. This Special Issue includes manuscripts that explore all stages of Quality Control testing for cosmetic products, i.e., (1) physicochemical stability testing; (2) microbial stability testing; (3) efficacy testing including objective/subjective claim substantiation testing and the evaluation of sensorial properties; (4) toxicological/safety testing with emphasis on current and evolving methodologies that replace animal testing.